Effect of Honey and Aqueous Garlic Extracts against Short-Term Exposure of Cigarette Tobacco Smoking in Mice: Histopathological and Biochemical Investigations - Ziad Shraideh; Darwish Badran; Ahmed Alzbeede (Journal of Toxicology, 2024)
It is well known that cigarette smoking adversely affects human health and induces oxidative stress in most vital organs. This study aims to assess the biochemical, histological, and ultrastructural values of honey and garlic extracts in ameliorating the effects of short-term exposure to cigarette smoke in mice. Forty-eight mice were randomly divided into six equal groups: group I was exposed to fresh air only, group II was exposed to cigarette smoke, group III was given 0.2 ml of honey extract, group IV was exposed to cigarette smoke and was given 0.2 ml of honey extract, group V was given 0.2 ml of garlic extract, and group VI was exposed to cigarette smoke and was given 0.2 ml of aqueous garlic extract. These exposures were repeated daily for 21 consecutive days among the treated groups. By the end of the third week, the animals were euthanized by physical cervical dislocation. Blood was taken for biochemical study, and the selected organs of the liver, kidney, and jejunum were processed for histological and ultrastructural studies. The biochemical results showed that short-term exposure of experimental mice to cigarette smoking did not alter the liver function tests except for decreasing the albumin level. Moreover, cigarette smoking elevates the concentration of carbonyl protein content and cystatin C. Histologically, the use of honey and garlic showed good protection to the liver, kidney, and jejunum, which was proved by transmission electron microscopy, in addition to lowering the oxidative stress biomarkers. In conclusion, using honey and/or garlic helps protect the liver, kidney, and jejunum against the hazardous effects of cigarette smoke.